Maternidade, de Eliseu Visconti: estudo da indumentária - Prado, Renata Cristina Garcia [UNIFESP] (2020)
This research intends to measure the dimensions of life and the plastic arts that not often appear articulated in academic works: painting and clothing, art and fashion, art history and fashion creation practice. The dissertation starts from the work of Eliseu Visconti, Maternity (1906), to make a comparative study, which shows how tensioned clothing can be presented within the graphic representation and also in the practice of fashion production. Firstly, it shows a description and analysis of the picture Maternity, changing its relations with an iconography of motherhood and breastfeeding from the 19th century until the beginning of the 20th century. Next, we discuss the history of women's clothing since the end of the 19th century, showing how the vestibule represented by the artist is articulated and not only to the values of the time, but also to support the characterization of the personages. At last, the final dissertation is dedicated to a practical application: a description of the fashion work that is used, with students from the technical course of the Technical course in Clothing Modeling at ETEC Tiquatira, from the Visconti framework.